1988
DOI: 10.1002/j.2048-7940.1988.tb00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Care of the Patient with Multiple Sclerosis

Abstract: Persons with the chronic illness of multiple sclerosis now live longer than ever. Rehabilitation nurses encounter many of these patients in their work, helping them adapt to the constraints and limitations imposed by the disease. Although a diagnosis of multiple sclerosis is characterized by uncertainty, much can be done to help patients and theirfamilies deal with the complications of the disease process, which may affect many areas of daily living. To provide comprehensive care, an understanding of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Just as there are ways to manage other disabilities, there are ways to manage constipation or fecal incontinence so that an individual will feel secure with bowel control at home and in the community. This security begins with a good nursing assessment, a clean bowel, and a daily focus on eight keys to success listed in : physical exercise, high fiber intake, high fluid intake, consistent habit time, an upright position on toilet or commode, privacy, medication management, and patient and family education (Bronstein, Popovich, & Stewart‐Amidei, 1991; Cannon, 1981; Doughty, 1996; Emick‐Herring, 1993; Gender, 1996; Hanak, 1992; Hickey, 1997; Kelly & Mahon, 1988; McConnell, 1988; Norton, 1997; Sharkey & Hanlon, 1989).…”
Section: Keys To Bowel Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as there are ways to manage other disabilities, there are ways to manage constipation or fecal incontinence so that an individual will feel secure with bowel control at home and in the community. This security begins with a good nursing assessment, a clean bowel, and a daily focus on eight keys to success listed in : physical exercise, high fiber intake, high fluid intake, consistent habit time, an upright position on toilet or commode, privacy, medication management, and patient and family education (Bronstein, Popovich, & Stewart‐Amidei, 1991; Cannon, 1981; Doughty, 1996; Emick‐Herring, 1993; Gender, 1996; Hanak, 1992; Hickey, 1997; Kelly & Mahon, 1988; McConnell, 1988; Norton, 1997; Sharkey & Hanlon, 1989).…”
Section: Keys To Bowel Successmentioning
confidence: 99%
“…Assigning a time for the bowel program consistent with an individual's preadmission bowel schedule should be one of the easiest ways to facilitate effective bowel functioning (Doughty, 1996; Venn, Taft, Carpentier, & Applebaugh, 1992). Most people have a bowel movement around the same time of day every one to three days, usually following a meal when the gastrocolic reflex moves ingested food through the gastrointestinal system and stimulates the bowel to empty its contents (Gender, 1996; Kelly & Mahon, 1988). Research by Kirshblum, Gulati, O'Connor, and Voorman (1998) found “most patients perform their bowel program in the morning, which is in contrast to an evening program commonly used in many acute rehabilitation settings” (p. 22).…”
Section: Keys To Bowel Successmentioning
confidence: 99%
“…Further cycles of inflammation and demyelination, however, may eventually render conduction along affected nerves impossible resulting in a concomitant loss of function (Kelly & Mahon, 1988;McDonald, 1994;Sibley, 1992). Diagnosis Traditionally diagnosed on the basis of clinical signs and symptoms, it has, at times, taken as long as seven years to conclusively diagnose MS (Hass, 1962).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Common primary effects include weakness, spasticity, fatigue, tremor, ataxia, pain, parasthesia, visual disturbances, cognitive changes, and bowel, bladder and sexual dysfimction (Kelly & Mahon, 1988;Schapiro, 1994;Warnell, 1991). Cachexia, decubitus ulcers, urinary tract infections, and contractures are some of the secondary effects of MS (Schapiro, 1994;Sibley, 1992;Whittington, 1983).…”
Section: Clinical Manifestationsmentioning
confidence: 99%